Globalization and the nation state : the impact of the IMF and the World Bank - Ranis, Gustav; Vreeland, James Raymond, 1971-; Kosack, Stephen, 1978- (Routledge studies in the modern world economy, 2006)
This book brings together an international team of contributors to assess the political economy of the IMF and World Bank programs. Contributors include Stephen Coate, Stephen Morris, Ravi Kanbur and Allen Drazen.